Untersuchungen zur dynamischen Kopplung der Troposphäre und der Stratosphäre - Kleppek, S. (2005)
Within the scope of this study a better understanding of the coupling of the troposphere and the stratosphere in the middle and polar latitudes (NH) on monthly timescales, caused by the propagation of quasi-stationary waves is improved. The approach was focused on the dynamical active winter months, including the largest variablity.The tropospheric variability is strongly affected by preferred circulation patterns, the so called teleconnection patterns. The most important, regional, tropospheric teleconnection patterns in the Northern Hemisphere are determined by means of a rotated EOF-Analyses of the geopotential height at the 500 hPa level. They can be attributed to three geographical regions; North Atlantic/Europe, Eurasia and Pacific/North America. These strongest tropospheric variability patterns are taken as the basic tropospheric quantities to analyse the connections between the tropospheric and stratospheric circulation. By means of instantaneous and time-lagged correlation analyses, it has been shown for the first time that different regional, tropospheric teleconnection patterns have different effects on the stratospheric circulation. The Pacific/North American patterns reveal significant correlation values with quasi-barotropic structures and the North Atlantic/European patterns show significant correlations over tropical and subtropical latitudes and invers correlation values over the polar region.The investigation of the stratospheric variability influence reveals that the strongest coupling of the North Atlantic/European teleconnection patterns with the stratospheric circulation appears during periods with a shift of the polar vortex towards Europe. The zonal averaged and particularly the local analyses of the wave propagation conditions show that weaker wind speed in the stratosphere over North America and the western part of the North Atlantic leads to improved wave propagation conditions in this geographical region. The stronger wave propagation produces a stronger interaction of the waves with ...